Monitoring Global Spread of Trademarks: Empiric Analysis - D. G. Galkin; I. N. Pospelova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The goal of the research is to elaborate recommendations dealing with shaping and using trademarks within the frames of national and international registration systems and to represent the condition and trends of trademark spread through analyzing data published by the World Organization of Intellectual Property and the national patent department (Rospatent). In the research such methods as deduction, scientific abstraction, logistic analysis and analogues were used. The authors study the national and international systems of trademarks registration. To show their interaction a universal model of developing and using trademarks was advanced. The article assesses the current global processes in spreading trademarks and compares the rates of filling applications for trademarks in the world and in Russia in 2010–2020. Countries were ranged by the number of application registrations, dynamics and structural changes in filling applications for trademarks among the Madrid system countries were described and the link between application filling and economic cycles was identified. The role of China and the place of Russia were depicted in modern trends of application filling according to the Madrid system. The authors think that the mentioned characteristics can help identify lines in trademarks spread within the short-term period.